Proceso de atención de enfermería en pacientes con pancreatitis aguda severa - Fajardo Nagua, Nelson Patricio; Rivas Montesinos, Andrés Nicolás (Machala : Universidad Técnica de Machala, 2019)
Introduction: Pancreatitis is the inflammation of the pancreas that is characterized histologically by the destruction of the acinar cells, whose origin results from an abnormal activation of the pancreatic enzymes causing the autodigestion of the gland and that, in general, requires hospitalization, manifests itself in acute or chronic form. Worldwide, the incidence per year ranges from 13 to 45 cases per 100,000 in the first, while in the second it varies between 5 to 12 per 100,000, the most common cause being biliary pancreatitis in 32-49%, followed by of the alcoholic with 20-31-8%, 10% is related to hyperlipemia, viral infections, pancreatic perfusion, impaired, ductal obstructions, drugs, hypercalcemia. Between 20-30% of patients with PA have a severe course, with the appearance of sepsis, respiratory distress syndrome, renal failure and multiorgan failure with a mortality rate of 25% due to complications derived. Case presentation: A 21-year-old female patient went to the Emergency Area at the Hospital Teófilo Dávila for presenting a clinical picture of 6 days of evolution characterized by moderate-intensity abdominal pain that has progressed at high intensity accompanied by nausea that carries to vomit several times, 24 hours ago thermal boost is added and not quantified and coordinated for the performance of laboratory tests, (white blood cells: 21.69 UL, neutrophils: 83.7%, lymphocytes: 8.9%, hematocrit: 38.6%, glucose: 113 mg / dl, total bilirubin: 1.61 mg / dL, direct bilirubin: 1.05 mg / dl, creatinine: 0.43 mg / dl, amylase of 1.322 UL and lipase of 1.319 U / L), whose results influenced hospital admission with diagnosis Severe acute pancreatitis physician to the intensive care unit General Objective: To analyze the case of a patient with severe acute pancreatitis through the review of the clinical history and the bibliographic search for the elaboration of nursing care plans that allow to restore their health. Method: The review of the patient's unique clinical history was made, as well as a bibliographic search in databases such as Pub Med, Scielo, Science Direct, Redalyc and NNN Consult, with the purpose of finding current scientific evidence regarding the case. Results: The findings of interest found as: age, sex, risk factors, clinical manifestations, diagnosis, laboratory tests (amylase / lipase), imaging studies, treatment and complications coincide significantly with that reported by researchers. . In this case, the patient was admitted to the ICU on November 13, 2018 for strict observation by the health personnel, its evolution was unsatisfactory. Conclusions: the theory of Virginia Henderson was taken into account, about the 14 basic needs of the human being, being the most affected: 2: feeding and hydration; 4: mobilization and 9: safety / protection, whose care plans were focused on the following nursing diagnoses: acute pain, risk of infection, nutritional imbalance, deterioration of physical mobility, and ineffective management of the therapeutic regimen. The process of nursing care applied in patients with severe acute pancreatitis, highlights the role of nursing professionals when considering this scientific method in the academic and work environment.
Introducción: La pancreatitis es la inflamación del páncreas que se caracteriza histológicamente por la destrucción de las células acinares, cuyo origen resulta de una activación anormal de las enzimas pancreáticas provocando la autodigestión de la glándula y que, por lo general, requiere hospitalización, se manifiesta en forma aguda o crónica. A nivel mundial la incidencia por año oscila entre 13 a 45 casos por cada 100.000 en la primera, mientras que en la segunda varía entre 5 a 12 por cada 100.000, siendo la causa más común la pancreatitis biliar en un 32-49%, seguida de la alcohólica con un 20-31-8%, el 10% se relaciona con hiperlipemias, infecciones virales, perfusión pancreática, deteriorada. Entre el 20-30% de los pacientes con pancreatitis aguda presentan un curso grave, generalmente con aparición de sepsis, síndrome de distrés respiratorio, insuficiencia renal y fallo multiorgánico con una tasa de mortalidad del 25% debido a las complicaciones derivadas. Presentación del caso: Paciente de 21 años de edad de sexo femenino acude al área de Emergencia en el Hospital Teófilo Dávila por presentar cuadro clínico de 6 días de evolución caracterizado por dolor abdominal de moderada intensidad que ha progresado a gran intensidad acompañado de náuseas que llevan al vómito por varias ocasiones, hace 24 horas se suma alza térmica no cuantificadas y se coordina para la realización de exámenes de laboratorio, (glóbulos blancos: 21.69 UL; neutrófilos: 83.7%; linfocitos: 8.9%; hematocrito: 38.6%; glucosa: 113 mg/dl, bilirrubina total: 1.61 mg/dL; bilirrubina directa: 1.05 mg/dl; creatinina: 0.43 mg/ dl, amilasa de 1.322 UL y lipasa de 1.319 U/L), cuyos resultados influenciaron para el ingreso hospitalario con diagnóstico médico de Pancreatitis aguda severa a la unidad de cuidados intensivos. Objetivo General: Analizar el caso de una paciente con pancreatitis aguda severa mediante la revisión de la historia clínica y la búsqueda bibliográfica para la elaboración de planes de cuidados de enfermería que permitan restaurar su salud. Método: Se hizo la revisión de la historia clínica única de la paciente, además de una búsqueda bibliográfica en bases de datos como: Pub Med, Scielo, Science Direct, Redalyc y NNN Consult, con el propósito de encontrar evidencia científica actual respecto al caso. Resultados: Los hallazgos de interés encontrados como: edad, sexo, factores de riesgo, manifestaciones clínicas, diagnóstico, exámenes de laboratorio (amilasa/lipasa), estudios de imagen, tratamiento y complicaciones coinciden significativamente con lo reportado por investigadores. En este caso, la paciente fue ingresada a UCI el 13 de noviembre del 2018 para observación estricta por el personal de salud, su evolución fue poco satisfactoria. Conclusiones: se tomó en cuenta la Teoría de Virginia Henderson, acerca de las 14 necesidades básicas del ser humano, siendo las más afectadas: 2: alimentación e hidratación; 4: movilización y 9: seguridad/protección, cuyos planes de cuidados estuvieron enfocados en los siguientes diagnósticos de enfermería: dolor agudo, riesgo de infección, desequilibrio nutricional, deterioro de la movilidad física, y manejo inefectivo del régimen terapéutico. El proceso de atención de enfermería aplicado en pacientes con Pancreatitis aguda severa, realza el rol de los profesionales de enfermería al considerar este método científico en el ámbito académico y laboral.
Keywords: PANCREATITIS AGUDA SEVERA; ATENCIÓN DE ENFERMERÍA; TEORIA DE VIRGINIA HENDERSON